2016
DOI: 10.1167/iovs.16-19945
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Optic Nerve Head Blood Flow in Normal Rats Evaluated by Laser Speckle Flowgraphy

Abstract: Mean blur rate in the rat ONH changed over time, increased from 10 to 19 weeks of age, then stabilized until 60 weeks. Mean blur rate of the total area exhibited regional differences: higher in the inferior quadrant than in the temporal quadrant. Laser speckle flowgraphy-Micro may provide reliable information for evaluating longitudinal changes of rat ONH blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…As no direct intervention on the gingiva was applied between 2 measurements, this CV could be considered an inherent component of clinical LSCI measurements. These values (5.4%‐6.0%) were very similar to the residual error of LSCI measurements in animal experiments where most clinical factors (retraction, reflection, most of the movements) can be eliminated. This suggests that it is difficult to further reduce this component which may include not only technical factors such as the selection of regions by visual inspection, motion artefacts, the internal error of the LSCI instrument, but also short‐term biological variation due to breathing, pulse, and vasomotion.…”
Section: Discussionsupporting
confidence: 74%
“…As no direct intervention on the gingiva was applied between 2 measurements, this CV could be considered an inherent component of clinical LSCI measurements. These values (5.4%‐6.0%) were very similar to the residual error of LSCI measurements in animal experiments where most clinical factors (retraction, reflection, most of the movements) can be eliminated. This suggests that it is difficult to further reduce this component which may include not only technical factors such as the selection of regions by visual inspection, motion artefacts, the internal error of the LSCI instrument, but also short‐term biological variation due to breathing, pulse, and vasomotion.…”
Section: Discussionsupporting
confidence: 74%
“…6A,B). The principle of LSFG-Micro is the same as that of LSFG, which was reported previously 8 . In brief, the mean blur rate (MBR), which represents a relative index of blood velocity, is determined by the blurring of the speckle pattern formed by the scattering of the laser by moving blood cells.…”
Section: Measurement Of Retinal Blood Flowmentioning
confidence: 68%
“…The development of flow regulation mechanisms with age, such as www.nature.com/scientificreports/ increase of myogenic tone of retinal vessels to adapt to the elevated perfusion pressure might also explain the unchanged retinal blood flow with increased OPP. Wada et al, in a longitudinal study of ONH blood flow in rats, reported an increase of resting ONH blood flow from 10 to 19 weeks of age and then the flow was stabilized until 60 weeks, whereas the OPP remained unchanged from 10 to 60 weeks 8 . The reasons for these inconsistent results with ours are unclear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations